Isaac newton: scientists who made history - Mason, Paul (Hodder Wayland London, 2002)
This title describes the life and career of Sir Isaac Newton. It compares the world before and after his life - giving a clear impression of the impact of his work and legacy. Science boxes explain the science behind his discoveries as well as an explanation of the Laws of Motion